A comparison of development methods used to define portion sizes in food-based dietary guidelines around the world - Salesse, Fanny; Eldridge, Alison L.; Mak, Tsz Ning; Gibney, Eileen R. (Frontiers in Nutrition, 2025)
IntroductionFood-based dietary guidelines (FBDGs) are essential public health tools for delivering dietary recommendations, and generally include guidance on portion sizes. Despite existing guidelines on developing and implementing FBDGs, there is still no consensus on best practices for their formulation. This paper compares the methodologies used by public health organizations to create FBDGs and examines how both methodology and geographical location may influence recommended portion sizes.MethodsDocuments on FBDG development were obtained from the Food and Agriculture Organization online repository of FBDGs, either directly from consumer-facing FBDG or from corresponding scientific reports. Methodological details in FBDG development were extracted and categorized. Recommended portions in grams per day were extracted for 15 food categories to enable comparison across development methods and global regions.ResultsFBDGs from 96 countries were accessed and translated. Of these, n = 83 were based on consensus/review, n = 15 used data-based approaches, and n = 30 included other minor calculations. Thirty-nine FBDGs were derived from a combination of consensus/review and another method. Of the countries providing portion size information, only one did not report its methodological approach. Comparisons of median portions sizes of food groups across methodologies showed no significant differences. Analyses across regions revealed that portion recommendations were generally consistent, with significant differences found only for one food group, namely, Fish & shellfish, where portion size recommendations were significantly higher in Europe compared to those in Latin America and the Caribbean.DiscussionResults indicate little variation in the recommendations for portion size across development methods, and for most food groups, across global regions. These findings suggest there is potential to harmonize portion size derivation in FBDGs at regional or global levels. However, further research is needed to assess whether harmonized guidance can apply to other aspects of FBDGs.